Internalization of Faith and Piety Values in the Formation of Personality Through Contemporary Science Learning - Arifudin, Iis; Khobir, Abdul; Syafeie, Ahmad Khomaini (Letiges, 2023)
Adolescents are in a transitional period where they seek their identity. Their thoughts and stances are constantly changing. If teenagers get good guidance from adults, they will become valuable people for themselves and their environment. Otherwise, they will be in doubt. Eventually, they will fall into a negative direction that will harm them. The purpose of this study is to explain the internalization of the values of faith and piety in the formation of personality through learning contemporary science. This research was conducted using a descriptive-analytic method with a quantitative approach. While the data collection steps used in this study were interviews, participatory observation, documentation studies, and questionnaires, The results of this study indicate that the teacher's efforts to internalize the values of faith and piety in the formation of student personality at Al Azhar 5 Islamic High School in Cirebon City through modern science learning, which includes praying before and after learning, reciting the Koran for 15 minutes the first hour before teaching and learning activities, and linking the subject matter to the content of faith and piety (imtaq), are categorized as very good based on student response data obtained by 82.2%. The obstacles faced by teachers in internalizing the values of faith and piety in the formation of students' personalities at SMA Islam Al Azhar 5 in Cirebon City through modern science learning include the lack of understanding of some teachers of non-Islamic religious education subjects in linking subjects with faith and piety.